Knowledge and practice on the use of metered dose inhalers by asthmatic patients seen at a Private General Practice in the Vhembe District, Limpopo Province - Magwentshu, Zolelwa Temperance (University of Limpopo (Medunsa Campus), 2010)
Background Asthma mortality in many countries is reported to be falling but the morbidity remains unacceptably high. One of the reasons for the latter is the reluctance to, and the inappropriate use of MDIs by patients resulting in inadequate dosing of medication and therefore poor asthma control. For family physicians to appropriately manage their asthmatic patients, they need to understand the patients’ knowledge and practice on the use of MDIs. Aim The aim of the study was to determine the knowledge and practice of asthmatic patients seen in a private general practice on the use of MDIs. Methodology A descriptive cross-sectional study was undertaken with fifty randomly selected participants. A structured questionnaire was used for data collection and data analysis was done using Microsoft Excel spreadsheet and SPSS version 17 software. Results Sixty percent (60%, n=30) of the participants were females and forty percent (40%, n=20) were males. The majority of the participants eighty two percent (82%, n=41) had asthma for more than five years. All the participants used MDIs. Ninety four percent (94%, n=47) used Asthavent® and 88% Budeflam®. Ninety four percent knew that Asthavent® was a reliever and only 20% knew that Budeflam® was a preventer. Conversely, forty percent (40%, n=20) thought that Budeflam® was a reliever. The majority of the participants were unable to correctly demonstrate the main steps in the practical use of the MDI. Conclusion The correct use of MDI was found to be poor for most participants. The majority of the participants lacked knowledge and skill for effective use of the MDI. The findings from this study provide reasons for family physicians to continuously educate their patients on the correct use of the MDI.
Thesis M.Med.(Family Medicine))--University of Limpopo (Medunsa Campus), 2010.
Keywords: Asthma; Inhalation